Hubungan Positif Pembiasaan Jalan Kaki dengan Jaminan Kualitas Tidur - Wahyudin Darmalaksana (Gunung Djati Conference Series, 2024)
This research aims to see the relationship between walking habits and ensuring sleep quality. This research conducted experiments to prove the findings of previous research. The results and discussion show that walking habits are positively related to ensuring sleep quality, which proves previous findings. The conclusion of this study is that there is a positive relationship between the habit of walking and significantly ensuring sleep quality.